Pt(II) and Ag(I) complexes with acesulfame: Crystal structure and a study of their antitumoral, antimicrobial and antiviral activities - Cavicchioli, Mauricio [UNESP]; Massabni, Antonio C. [UNESP]; Heinrich, Tassiele A.; Costa-Neto, Claudio M.; Abrão, Emiliana Pereira [UNESP]; Fonseca, Benedito A. L.; Castellano, Eduardo E.; Corbi, Pedro P.; Lustri, Wilton R.; Leite, Clarice Queico Fujimura [UNESP] (Elsevier B.V., 2010)
Two new complexes of platinum(II) and silver(I) with acesulfame were synthesized. Acesulfame is in the anionic form acesulfamate (ace). The structures of both complexes were determined by X-ray crystallography. For K(2)[PtCl(2)(ace)(2)] the platinum atom is coordinated to two Cl(-) and two N-acesulfamate atoms forming a trans-square planar geometry. Each K(+) ion interacts with two oxygen atoms of the S(=O)(2) group of each acesulfamate. For the polymeric complex [Ag(ace)](n) the water molecule bridges between two crystallographic equivalent Agl atoms which are related each other by a twofold symmetry axis. Two Agl atoms, related to each other by a symmetry centre, make bond contact with two equivalent oxygen atoms. These bonds give rise to infinite chains along the unit cell diagonal in the ac plane. The in vitro cytotoxic analyses for the platinum complex using HeLa (human cervix cancer) cells show its low activity when compared to the vehicle-treated cells. The Ag(I) complex submitted to in vitro antimycobacterial tests, using the Microplate Alamar Blue (MABA) method, showed a good activity against Mycobacterium tuberculosis, responsible for tuberculosis, with a minimal inhibitory concentration (MIC) value of 11.6 mu M. The Ag(I) complex also presented a promising activity against Gram negative (Escherichia colt and Pseudomonas aeruginosa) and Gram positive (Enterococcus faecalis) microorganisms. The complex K(2)[PtCl(2)(ace)(2)] was also evaluated for antiviral properties against dengue virus type 2 (New Guinea C strain) in Vero cells and showed a good inhibition of dengue virus type 2 (New Guinea G strain) replication at 200 mu M, when compared to vehicle-treated cells. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Antitumor agents; Antibiotic; Acesulfame-K; Platinum; Silver